Teachers' perception of children's agency in early childhood education - Thomayer, Claudia (2017)
The concept of agency is currently brought more and more into the focus of ed- ucational research. While professional agency at work is for instance already broadly discussed in adult education, research on children’s agency is still in its infancy. Children’s agency can be viewed from every aspect of children’s life, the focus of this research will be on early childhood education (ECE). For this study, children’s agency is examined from the teachers’ point of view. Five open-ended interviews were carried out with ECE teachers working in different kindergartens in Vienna, Austria. Additionally, one interview was held with two regional managers of the largest provider of kindergartens in Vienna. All interviews were conducted in the summer of 2016 and were ana- lysed using content analysis. The results were not only discussed regarding general agency, but also under consideration of the Capability Approach (CA). The results indicate that children’s agency, in general, is supported by kindergarten teachers in kindergartens in Austria. The teachers receive much support in doing so, but they were also naming some hindering framework conditions. The outcomes of practiced agency in an early age are described widely positive, though certain restrictions on children’s freedom of choice are seen as necessary. This study can not only implicate a change in society and other ECE teachers’ perception on the importance of promoting children’s agency but hopefully will also bring about further research on the issue.